Strengthening the Quality of Islamic Education through Ihsan-Based Management Strategies - Yuli Maulana; Irawan; Rohmat Mulyana Sapdi (Al-Qalam Institue, 2026)
The transformation and increasing demands for quality improvement in Islamic education require a management model that extends beyond structural and administrative orientations to incorporate spiritual and ethical values. Ihsan, as a fundamental Islamic principle, offers a relevant foundation for educational management practices. This study aims to analyze the implementation of ihsan-based management strategies in improving the quality of Islamic education at Madrasah Diniyah Takmiliyah (MDT) Al-Hidayah Pasir Biru, Cibiru District, Bandung City. Employing a qualitative approach with a field research design, data were collected through in-depth interviews with institutional managers and key stakeholders. The data were analyzed thematically based on established indicators of Islamic education quality, including teacher professionalism, curriculum and learning processes, facilities and infrastructure, as well as learning evaluation and assessment. The findings reveal that ihsan-based management is systematically implemented and functions as a managerial ethos that promotes continuous and holistic quality improvement. Core values such as responsibility, trustworthiness, sincerity, and fairness underpin institutional management practices and contribute positively to both graduate quality and public trust. The study implies that ihsan-based management can be operationalized as a sustainable, context-sensitive strategy for enhancing the quality of Islamic education and may serve as a conceptual model for similar Islamic educational institutions